Workplace Exposures - Lee, Janet T.; Gaertner, Wolfgang B. (Clinics in Colon and Rectal Surgery, 2019)
Workplace exposure in colorectal surgery is unique compared with other surgical specialties and generally underreported. Although the most common device-associated exposure in surgery is suture needle injury, colorectal surgeons are increasingly exposed to gastrointestinal-related infectious agents, radiation, and other hazards in multiple different clinical settings. Highlighting the unique workplace exposures in colorectal surgery may help increase awareness, improve education, and identify possible targets for early intervention in order to minimize these risks.
Keywords: workplace exposure; needlestick injury; infectious risk; system-based practice; colon and rectal surgery